2004
DOI: 10.1038/sj.emboj.7600065
|View full text |Cite
|
Sign up to set email alerts
|

Synergy and antagonism between Notch and BMP receptor signaling pathways in endothelial cells

Abstract: Notch and bone morphogenetic protein signaling pathways are important for cellular differentiation, and both have been implicated in vascular development. In many cases the two pathways act similarly, but antagonistic effects have also been reported. The underlying mechanisms and whether this is caused by an interplay between Notch and BMP signaling is unknown. Here we report that expression of the Notch target gene, Herp2, is synergistically induced upon activation of Notch and BMP receptor signaling pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
210
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(223 citation statements)
references
References 43 publications
12
210
1
Order By: Relevance
“…Expression of constitutively active Notch inhibits differentiation of neural and myogenic cells and promotes generation of hematopoietic stem cells (60 -62). Very recent studies have shown that BMP and Notch signaling do collaborate during differentiation of myogenic and endothelial cells and that Hey1 is a crucial player in this collaboration (63,64). Our data in osteoblast cells show that even transient inhibition of Hey1 expression leads to enhanced matrix mineralization, a sign of their maturation, by osteoblast.…”
Section: Microarray Analyses Of Genome-wide Gene Expression Insupporting
confidence: 58%
“…Expression of constitutively active Notch inhibits differentiation of neural and myogenic cells and promotes generation of hematopoietic stem cells (60 -62). Very recent studies have shown that BMP and Notch signaling do collaborate during differentiation of myogenic and endothelial cells and that Hey1 is a crucial player in this collaboration (63,64). Our data in osteoblast cells show that even transient inhibition of Hey1 expression leads to enhanced matrix mineralization, a sign of their maturation, by osteoblast.…”
Section: Microarray Analyses Of Genome-wide Gene Expression Insupporting
confidence: 58%
“…It is well established that Hes1 expression can be regulated by Notch/Rbpjκ-independent signaling before E8.5 (Hatakeyama et al, 2004;Kageyama et al, 2005). Additionally, Rbpjκ-independent expression of Notch factors, including Hes genes, can be mediated by members of the BMP (Dahlqvist et al, 2003;Itoh et al, 2004) Kadesch, 2001), WNT/β-catenin (Axelrod et al, 1996;Hayward et al, 2005) and Shh (Wall et al, 2009) pathways throughout embryonic development. However, only a few studies have shown that Hes5 can be modulated by Notch/Rbpjκ-independent signaling occurring at two distinct time points: before E8.5 (Donoviel et al, 1999;Hitoshi et al, 2011) and during adult neurogenesis (Matsuda et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-b or BMP induces the expression of several genes that are also known target genes for Notch1, such as Hes-1 (Blokzijl et al, 2003), Hey1 (Zavadil et al, 2004), Hes-5 (Takizawa et al, 2003), Herp2 (Itoh et al, 2004) and the Notch ligand Jagged1 (Zavadil et al, 2004). However, information as to whether Notch1 or Notch4 can modify the TGF-b signaling pathway and the response of cells to TGF-b is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In Blokzijl's study (2003) (Takizawa et al, 2003) and Herp2 (Itoh et al, 2004). Takizawa et al (2003) showed that BMP2 enhances the expression of Hes5 in mouse neuroepithelial cells.…”
Section: Effects Of Tgf-b1 or Bmp-2 On Notch Signaling During Developmentioning
confidence: 99%
See 1 more Smart Citation